Safety assessment of laronidase: real-world adverse event analysis based on the FDA adverse event reporting system (FAERS) - Zhuomiao Lin; Junling Xue; Meiqing Yang; Xihui Yu; Jiahong Zhong (Frontiers in Pharmacology)
ObjectiveLaronidase is the first drug of enzyme replacement therapy approved for the treatment of mucopolysaccharidosis type I (MPS I). However, its adverse events (AEs) have not been investigated in real - world settings. The aim of this study was to investigate AEs associated with laronidase using the Food and Drug Administration Adverse Event Reporting System (FAERS).MethodsData for laronidase were acquired from the FAERS database covering Q1 2004 through Q4 2024. The Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN) and Multi-item Gamma Poisson Shrinker (MGPS) were employed to identify potential safety signals.ResultsA total of 3,677 adverse event reports associated with laronidase were identified in the FAERS from 2004 to 2024. The results revealed that common AEs of laronidase such as pyrexia [n = 465, ROR = 6.23 (5.68–6.83)], pneumonia [n = 223, ROR = 3.22 (2.82–3.68)], cough [n = 167, ROR = 2.78 (2.38–3.23)], influenza [n = 114, ROR = 4.95 (4.12–5.95)], urticaria [n = 106, ROR = 2.99 (2.47–3.62)], disease progression [n = 101, ROR = 3.95 (3.25–4.81)]. Furthermore, we detected probable unexpected AEs like seizures [n = 75, ROR = 3.1 (2.47–3.89)], hydrocephalus [n = 60, ROR = 50.47 (39.1–65.14)], blindness [n = 44, ROR = 5.02 (3.73–6.75)], glaucoma [n = 32, ROR = 7.56 (5.34–10.69)]. Laronidase -induced adverse reactions involved 27 System Organ Class (SOC). No significant difference in AEs was observed between sexes for laronidase. Most AEs (n = 763) emerged more than 360 days following laronidase treatment.ConclusionOur study has identified AEs associated with laronidase that could provide support for clinical monitoring and risk identification of laronidase.